Influences of Sex and Age on the Hematological Profile of the Jundia (Silver Catfish) Rhamdia quelen - Nascimento, Nivaldo Ferreira do [UNESP]; Okada Nakaghi, Laura Satiko [UNESP]; Hilbig, Cleonice Cristina; Ventura, Arlene Sobrinho; Barni de Azevedo, Ana Carolina; Dean, Andressa Fierli; Bombardelli, Robie Allan (Taylor & Francis Inc, 2016)
In this study, sex and age influenced the hematological profiles of Jundia (Silver Catfish) Rhamdia quelen. Females showed lower levels of hemoglobin, young fish increased lymphocyte counts, and older fish increased hematocrit values. These results indicate that, depending on age and sex, the fish have disparate hematological profiles. For this reason, it is important to consider the sex and age of an R. quelen when examining the impact of environmental and management factors on this species in terms of their hematological profiles.